Análise óptica e térmica do receptor de um sistema de concentradores Fresnel lineares - Scalco, Patricia (Universidade do Vale do Rio dos Sinos, 2016)
The study of different energy sources is extremely important, both in economic and social scope, as well as in the environmental field. Thus, the use of solar energy for the generation of heat to feed processes that require temperatures around 300 ºC appears as an alternative to supply the use of fossil fuels in industrial environments, either partially or totally. To reach this temperature range, high-performance equipment must be used that can concentrate solar radiation to the maximum. Thus, Fresnel linear reflector technology is used, which uses the principle of solar concentration, where the solar rays focus on mirrors that reflect this radiation to the receiver. The receiver is composed of an absorber tube and a second reflecting surface whose function is to maximize the number of rays absorbed by the receiver. This type of installation has been competitive in comparison to other types of solar concentration because of its simple structure, low cost and easy maintenance. Thus, in this work will be analyzed optical and thermal aspects of the receiver set for the trapezoidal and the CPC secondary concentrator. For this, the study was divided into two stages. In the first stage the ray tracing was done for the two geometries of the secondary concentrator studied in order to determine the interception factor and the optical losses involved in this process. In addition, the influence of insertion of a glass surface on the base of the receptor was isolated by isolating it from the environment. The second stage consisted of the thermal analysis, where the heat transfer study was carried out in the receiver in order to determine the efficiency of the system as well as the factors that influence the performance of the system. In the geometric analysis, the interception factor for the trapezoidal secondary concentrator was 36% for the open receptor and 45% for the receptor with the glass enclosure. For the CPC secondary concentrator, the results were 44% for the open receptor and 56% for the receptor with the glass enclosure. Through the thermal analysis, it was possible to establish the efficiency of the system, which, for the best working condition, DNI of 1000 W/m², was 80%.
Keywords: Refletores fresnel lineares; Concentrador secundário; Traçado de raios; Transferência de calor; Linear fresnel reflector; Secondary concentrator; Ray tracing; Heat transfer; ACCNPQ::Engenharias::Engenharia Mecânica